1984
DOI: 10.2527/jas1984.593717x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Level of Feed Intake on Nitrogen, Amino Acid and Energy Digestibilities Measured at the End of the Small Intestine and over the Total Digestive Tract of Growing Pigs

Abstract: A replicated trial of 3 X 3 Latin square design was conducted with growing pigs (about 29 kg initially) to determine the effects of different levels of feed intake on nutrient digestibilities determined near the end of the small intestine and over the total digestive tract. Pigs were fiftted with simple T-cannula. Feeding levels were ad libitum (AL) and limit-fed (4.5 or 3% of body weight/d). A 16% sorghum-soybean diet was used. Limit-fed pigs were fed at 12-h intervals and water was limited to 2 liters/kg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 10 publications
8
24
2
Order By: Relevance
“…This may due to the different nutrient availability of various ingredient sources. The ATTD of DM, and GE and ME (%) for CSBM based diets were similar as the previous study (Chapter 2); whereas, likely due to the lower FI (Haydon et al, 1984), the apparent CP digestibility estimates were approximately 2% greater than the previous study (Chapter 2).…”
Section: Nutrient Digestibility and Energy Values Of Dietssupporting
confidence: 74%
See 2 more Smart Citations
“…This may due to the different nutrient availability of various ingredient sources. The ATTD of DM, and GE and ME (%) for CSBM based diets were similar as the previous study (Chapter 2); whereas, likely due to the lower FI (Haydon et al, 1984), the apparent CP digestibility estimates were approximately 2% greater than the previous study (Chapter 2).…”
Section: Nutrient Digestibility and Energy Values Of Dietssupporting
confidence: 74%
“…At lower FI, the longer retention time (Seerley et al, 1962) and less non-protein substrate for microbes' requirement may result in increased deamination of AA by microbes and absorption of the large intestine (Fuller and Reeds, 1998 and Stein, 2004). In contrast, Haydon et al (1984) reported decreased energy digestibility with increasing FI. Harris et al (2012) selected pigs based on their residual feed intake (RFI), and concluded that the digestibility values for DM, CP, and GE were greater in the low vs. high RFI pigs; whereas, P digestibility did not differ between the pig lines.…”
Section: Feed Intakementioning
confidence: 75%
See 1 more Smart Citation
“…Our proline flow of 6.1 g/kg DM intake approaches the upper limit and is considerably higher than the average value of 1.31 given by Jansman et al (2002). There are numerous factors affecting the endogenous flow of AA such as body weight (Leterme and Théwis, 2004), feed intake (Haydon et al, 1984), dietary fibre (Taverner et al, 1981) or duration of the feeding of N-free diet (Hodgkinson et al, 2000). The present results as well as those of Hess and Sève (1999) suggest that pig individuality may also be a significant source of variation.…”
Section: Resultsmentioning
confidence: 48%
“…These results are in agreement with earlier reports (Affentranger et al, 1996;Akdag et al, 2008). Nutrient digestibility increases with level of feed intake (Haydon et al, 1984) and the absorbed nutrients are used for maintenance and lean gain (Scharlach & Kleyn, 1996). When energy consumption exceeds requirements, the extra energy is converted to fat and stored (Scharlach & Kleyn, 1996).…”
Section: Resultsmentioning
confidence: 99%